Prevalence and Outcomes of Gastrointestinal Anomalies in Down Syndrome - Elgendy, Marwa M.; Cortez, Josef; Saker, Firas; Mohamed, Mohamed A.; Aly, Hany (American Journal of Perinatology, 2024)
Objectives Our objective was to investigate the prevalence of small intestinal atresia and Hirschsprung's disease (HD) in infants with Down syndrome (DS) and its impact on outcomes.Study Design We analyzed the National Inpatient Sample dataset. We included infants with DS, small intestinal atresia, HD, and the concomitant occurrence of both conditions. Regression analysis was used to control clinical and demographic variables.Results A total of 66,213,034 infants were included, of whom, 99,861 (0.15%) had DS. The concomitant occurrence of small intestinal atresia and HD was more frequent in infants with DS compared with the general population, adjusted odds ratio (aOR): 122, 95% confidence interval (CI): 96–154, (p < 0.001). Infants with DS and concomitant small intestinal atresia and HD had higher mortality compared with those without these conditions, aOR: 8.59, 95% CI: 1.95–37.8.Conclusion Infants with DS are at increased risk of concomitant small intestinal atresia and HD, and this condition is associated with increased mortality.Key Points
Keywords: Hirschsprung's disease; duodenal atresia; trisomy 21; mortality